Clinical enzymes inhibitory activities, antioxidant potential and phytochemical profile of Vernonia oligocephala (DC.) Sch.Bip. ex Walp roots. (March 2019) - Mahmood, Waqas; Saleem, Hammad; Shahid, Wardah; Ahmad, Irshad; Zengin, Gokhan; Mahomoodally, Mohamad Fawzi; Ashraf, M.; Ahemad, Nafees
Abstract: We investigated into the different solvent extracts (methanol, dichloromethane, ethyl acetate, n- hexane and n -butanol) of Vernonia oligocephala (DC.) Sch.Bip. ex Walp roots for their phytochemical composition, antioxidant and enzyme inhibition potential. Phytochemical analysis showed the presence of flavonoids, saponins, terpenoids, and phenolics as secondary metabolites. Methanol extract exhibited the highest phenolic (113.11 mg GAE/g) and flavonoid (97.35 mg QE/g) contents as well as ferric reducing antioxidant power (71.92 GAE/g). The ethyl acetate extract exhibited maximum DPPH (IC50 ; 39.11 μg/mL), total antioxidant capacity (73.07 mg GAE/g) and urease inhibition (IC50 ; 55.89 μg/mL). The n -hexane fraction was most active against cholinesterases. All extracts showed least activity against tyrosinase and lipoxygenase (except butanol fraction, IC50 : 132.2 μg/mL). This study showed that V. oligocephala extracts can be regarded as perspective material for isolating bioactive molecules. Highlights: First study of extracts of V. oligocephala root for their phytochemical, antioxidant and enzyme inhibition potential. High polyphenolic contents were observed for methanol extract. Ethylacetate fraction showed strong antioxidant, butrylcholinesterase and urease inhibition activities. V. oligocephala possess excellent biological potential.